Distribusi Zakat dalam Menumbuhkan Kesejahteraan Masyarakat Sidowungu Gresik Jawa Timur - Sutono Sutono; Ayu Rosalia Indah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Welfare for the poor is the most important topic in improving citizens. Islam as Ad-diin has offered several teachings for humans that apply universally with two dimensional characteristics, namely happiness and well-being in life in this world and in the hereafter. In the concept of the modern world, welfare is a condition where a person can fulfill basic needs, be it the need for food, clothing, shelter, clean drinking water as well as the opportunity to continue education and have adequate work that can support the quality of life so as to have a social status that leads to the same social status as other citizens. ZIS as an extension of the government in helping the needs of the poor with the aim of improving the welfare of the community who initially as zakat recipients turned into zakat givers, so that later the funds used will be evenly distributed and felt by the wider community. as well as purifying assets that may be accidentally mixed with assets that are forbidden for consumption. The urgency of ZIS in Sidowungu is one of the main elements of effective and efficient zakat management in order to realize the welfare of the community. As for the discussion of this article about the welfare pattern for the poor as the process of distributing ZIS funds in Sidowungu Village. The method used in this article is a quantitative approach. The subjects of this study were 165 poor people in Sidowungu Village, while the sample size was 65 poor people using probability sampling. The results of the study, processed using the PASW SPSS 23 for Windows program, showed that partial test results for H0 were rejected and H1 was accepted if the calculated t value was greater than the table t value or the sig value was less than 0.05. This means that the distribution of funds partially affected the welfare of the poor in Sidowungu Village. The magnitude of the influence between variables can be seen from the coefficient of determination of 0.079, meaning that 79.0% of the welfare of the poor in Sidowungu Village was influenced by the distribution of ZIS funds, while the remaining 21.0% was influenced by other variables not included in this study.